2022
DOI: 10.3389/fnins.2022.996325
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity between primary motor cortex subregions and the whole brain in patients with incomplete cervical spinal cord injury

Abstract: To investigate the reorganizations of gray matter volume (GMV) in each subregion of primary motor cortex (M1) after incomplete cervical cord injury (ICCI) and to explore the differences in functional connectivity (FC) between the M1 subregions and the whole brain, and further to disclose the potential value of each M1 subregion in motor function rehabilitation of ICCI patients. Eighteen ICCI patients and eighteen age- and gender- matched healthy controls (HCs) were recruited in this study. The 3D high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recently, studies using rs-fMRI in SCI have increased. There are many reports in humans ( Choe et al, 2013 ; Hou et al, 2014 , 2016 ; Chisholm et al, 2015 ; Min et al, 2015a , b ; Zhu et al, 2015 ; Oni-Orisan et al, 2016 ; Kaushal et al, 2017 ; Pan et al, 2017 ; Chen et al, 2018 ; Hawasli et al, 2018 ; Ge et al, 2019 ; Karunakaran et al, 2020 ; Li et al, 2020a , b , 2023 ; Park et al, 2020 ; Black et al, 2021 ; Huynh et al, 2021 ; Nakanishi et al, 2021 ; Zheng et al, 2021 , 2022 ; Guo et al, 2022 ; Kim et al, 2022 ; Vallesi et al, 2022 ; Wang et al, 2022 ; Mandloi et al, 2023 ) and several reports in nonhuman primates ( Rao et al, 2014 , 2016 , 2022 ; Wu et al, 2017 ) and rodents ( Seminowicz et al, 2012 ; Matsubayashi et al, 2018 ; Wu et al, 2020 ; Sanganahalli et al, 2021 , 2022 ). The analysis of rs-fMRI in SCI seems to be in its infancy due to differences in the various rs-fMRI analysis methods (seed-based, ICA, graph theory, ReHo, ALFF, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies using rs-fMRI in SCI have increased. There are many reports in humans ( Choe et al, 2013 ; Hou et al, 2014 , 2016 ; Chisholm et al, 2015 ; Min et al, 2015a , b ; Zhu et al, 2015 ; Oni-Orisan et al, 2016 ; Kaushal et al, 2017 ; Pan et al, 2017 ; Chen et al, 2018 ; Hawasli et al, 2018 ; Ge et al, 2019 ; Karunakaran et al, 2020 ; Li et al, 2020a , b , 2023 ; Park et al, 2020 ; Black et al, 2021 ; Huynh et al, 2021 ; Nakanishi et al, 2021 ; Zheng et al, 2021 , 2022 ; Guo et al, 2022 ; Kim et al, 2022 ; Vallesi et al, 2022 ; Wang et al, 2022 ; Mandloi et al, 2023 ) and several reports in nonhuman primates ( Rao et al, 2014 , 2016 , 2022 ; Wu et al, 2017 ) and rodents ( Seminowicz et al, 2012 ; Matsubayashi et al, 2018 ; Wu et al, 2020 ; Sanganahalli et al, 2021 , 2022 ). The analysis of rs-fMRI in SCI seems to be in its infancy due to differences in the various rs-fMRI analysis methods (seed-based, ICA, graph theory, ReHo, ALFF, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…( Margulies et al, 2010 ; Lv et al, 2018 ), the timing of imaging, and degree of injury, and the lack of sufficient evidence based on animal experiments. For example, while reports of intra-insular network involvement in pain after SCI show similar tendencies ( Li et al, 2020a , b ; Huynh et al, 2021 ; Mandloi et al, 2023 ), reports of changes in motor cortex connectivity in relation to motor function are inconsistent ( Hou et al, 2014 ; Min et al, 2015a , b ; Zhu et al, 2015 ; Hou et al, 2016 ; Oni-Orisan et al, 2016 ; Rao et al, 2016 ; Kaushal et al, 2017 ; Pan et al, 2017 ; Hawasli et al, 2018 ; Matsubayashi et al, 2018 ; Li et al, 2020a,b ; Park et al, 2020 ; Nakanishi et al, 2021 ; Kim et al, 2022 ; Wang et al, 2022 ). In the present study, network analysis revealed a shift in main hub function from the pyramidal/cortical to the extrapyramidal/subcortical system.…”
Section: Discussionmentioning
confidence: 99%